Circulating free DNA as a diagnostic marker for echinococcosis: a systematic review and meta-analysis - Luo, Xiaoqin; Jiang, Ping; Ma, Jideng; Li, Zian; Zhou, Jianwu; Wei, Xiaoxing; A, Jide; Chai, Jinping; Lv, Yanke; Cheng, Peng; Cao, Chunhua; A, Xiangren (Frontiers in Microbiology, 2024)
Echinococcosis is a chronic zoonotic disease caused by tapeworms of the genus Echinococcus. The World Health Organization (WHO) has identified encapsulated disease as one of 17 neglected diseases to be controlled or eliminated by 2050. There is no accurate, early, noninvasive molecular diagnostic method to detect echinococcosis. The feasibility of circulating free DNA as a diagnostic method for echinococcosis has been inconclusive in the results of a number of published studies, but to date there have been no systematic evaluations assessing the overall performance of these assays. We report here the first meta-analysis assessing the diagnostic accuracy of cfDNA in plasma, serum and urine for echinococcosis.We systematically searched PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI) and WeiPu databases up to January 17, 2024 for relevant literature. All analyses were performed using RevMan 5.3, Meta-DiSc 1.4、Stata 17.0 and R 4.3.1 software. The sensitivity, specificity and other indicators of accuracy of circulating cfDNA for the diagnosis of echinococcosis were summarized. Subgroup analyses and meta-regression were performed to identify sources of heterogeneity.Results: A total of seven studies that included 218 patients with echinococcosis and 214 controls (156 healthy controls, 32 other disease controls (non-hydatid patients), and 26 non-study-targeted echinococcosis controls were included).Summary estimates of the diagnostic accuracy of cfDNA in the diagnosis of echinococcosis were as follows: sensitivity (SEN), 0.51 (95% CI, 0.45-0.56); specificity (SPE), 0.99 (95% CI, 0.97-0.99); positive likelihood ratio (PLR), 11.82 (95% CI,; negative likelihood ratio (NLR), 0.57 (95% CI, 0.41-0.80); diagnostic ratio (DOR), 36.63 (95% CI,; and area under the curve (AUC), 0.98 (95% CI, 0.96-1.00).Existing evidence indicates that the combined specificity of circulating cfDNA for echinococcosis is high. However, the combined sensitivity performance is unsatisfactory due to significant inter-study heterogeneity. To strengthen the validity and accuracy of our findings, further large-scale prospective studies are required.